Is the labor market vulnerability of less-educated men rally about job competition? New insights for the United States - Gesthuizen, Maurice [Verfasser]; Solga, Heike [Verfasser] (My University, 2014)
"There are various reasons why less-educated men have higher risks of labor market vulnerability—risks such as being unemployed or, if employed, having only low socioeconomic status. The commonly used argument is that these higher risks result from increased job competition caused by an oversupply of higher educated workers, who displace the less-educated from their jobs. In addition to exploring this argument, we investigate the impact of less-educated men’s cognitive skills, their social resources, and the (historically embedded) signaling value of not having educational credentials. We study this impact by using institutional and compositional variations across labor market entry cohorts in the United States. For our analyses, we use the data of the 1974–2008 US General Social Survey (GSS). They show that an oversupply of high-educated workers mainly increases the unemployment risks of the higher-educated themselves. In labor market entry cohorts where the negative selection on parental background of the group of less-educated is more pronounced, the less-educated run a relatively high risk of unemployment." (authors abstract)

"Es gibt verschiede Gründe, warum schlechter ausgebildete Männer höheren Risiken der Arbeitsmarktverwundbarkeit - Arbeitslosigkeitsrisiken oder bei Beschäftigten ein niedriger sozioökonomischer Status - unterliegen. Die gebräuchliche Erklärung hierfür ist, dass der Grund für diese höheren Risiken ein gesteigerter beruflicher Wettbewerb ist, der auf ein Überangebot an besser ausgebildeten Arbeitskräften zurückzuführen ist, die die schlechter ausgebildeten Arbeitskräfte aus ihren Beschäftigungen verdrängen. Zusätzlich zur Untersuchung dieser Erklärung analysieren wir den Einfluss der kognitiven Fähigkeiten schlechter ausgebildeter Männer, ihre sozialen Ressourcen und den (historisch eingebetteten) Signalwert, über keine Bildungsnachweise zu verfügen. Wir untersuchen diese Auswirkungen mittels institutioneller und kompositioneller Variationen über Arbeitsmarkt-Eintrittskohorten hinweg in den USA. Für unsere Analysen nutzen wir die Daten des 1974-2008 US General Social Survey (GSS). Sie zeigen, dass ein Überangebot an gut ausgebildeten Arbeitskräften hauptsächlich die Arbeitslosigkeitsrisiken der besser ausgebildeten Personen selbst steigert. In Arbeitsmarkt-Eintrittskohorten, in welchen die negative Selektion basierend auf dem Hintergrund der Eltern der Gruppe der schlechter ausgebildeten deutlicher ist, haben die schlechter ausgebildeten ein relativ hohes Arbeitslosigkeitsrisiko." (Autorenreferat, BIBB-Doku)
Handelt es sich bei der Arbeitsmarktverwundbarkeit schlechter ausgebildeter Männer wirklich um beruflichen Wettbewerb? Neue Einblicke aus den USA
Keywords: P 1.4 Männer; P 2.2 An- und Ungelernte; G 1.2 Arbeitsmarkt; I 2.3.2 Nordamerika; Arbeitsmarktrisiko; Männer; Geringqualifizierter; Substitution; Panel; USA